Desain Pembuatan Barrier Guna Mengurangi Kebisingan Kereta Api Akibat Double Track Jalur Kereta Api Di Area Pemukiman Lintas Manggarai - Bekasi - Arista, Eka; P, Rianto Rili (Politeknik Perkeretaapian Indonesia Madiun, 2017)
One effort to reduce noise levels is urban planning. However, in big cities this is often not achieved due to population growth and the unavailability of balanced land. So that houses and buildings must be built close together and even close to the railroad tracks. All long-distance trains to the East (West Java, Central Java, East Java and Yogyakarta Special Region), both economy class, business and executive trains departing from Jakarta Kota Station, Pasar Senen Station and Gambir Station will pass through Bekasi Station until with Cirebon Station. From the data on the number of train trips according to the 2015 Train Travel Chart (Gapeka), there are approximately 122 trips each day. Train activities with frequent travel frequencies throughout the day can cause positive and negative externalities. Positive externalities felt by people who live close to trains include savings in transportation costs and ease and speed of access. The negative externalities, namely noise pollution, safety, and the risk of crime in the form of stone throws. Noise is one parameter to measure environmental quality